The Heist : Fox and O Hare #1 - Evanovich, Janet; Goldberg, Lee, 1962-; Brick, Scott (New York : Random House Audio, 2013)
FBI Special Agent Kate Winslow uses her own schemes to outmaneuver charming con man Danny Cole, who becomes an unlikely partner when her next mission pits her against a formidable adversary.
Unabridged.
Compact discs.
Read by Scott Brick.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Intelligence service -- United States -- Fiction; Government investigators -- Fiction; Romantic suspense fiction; Audiobooks